Evaluation of the large-scale prevention program of violence in adolescent relationships - Ajduković, Dean; Sušac, Nika; Löw Stanić, Ajana (2012)
The purpose of this study was to evaluate the effectiveness of a large-scale prevention program of violence in adolescent romantic relationships that was delivered to 5.150 secondary school students aged 16-17 in Croatia. The method was quasi-experimental pre-post test design with two groups. The participants were 1.587 adolescents from 82 schools (829 students in the intervention condition and 758 in the comparative group of classes). The intervention included 4 interactive workshops of 45 minutes each, delivered to whole classes during regular school hours . The topics addressed in the workshops included: beliefs about healthy and safe relationship, recognition of violence in youth relationships, knowledge about own rights in a relationship, awareness of own victimization and perpetration of violence in a relationship, setting boundaries in an unsafe relationship and seeking and providing help in case of violence in a relationship. The effect of the workshop delivery on these topics was assessed using the respective instruments with good metric properties . Four to six months after workshop delivery, the participants in the intervention classes reported statistically significant improvements: perpetrating and experiencing less violent behaviors, improved beliefs about healthy and quality relationships, better recognition of violent behaviors and knowledge of rights in a relationship. The effect size for reduction of overall perpetration was moderate and consistent for all three aspects of violent behaviors (physical, psychological and sexual). The effect size for victimization was smaller, with effective decrease in physical and sexual victimization. Our results suggest that a preventive program with only four one-hour workshops is effective in reducing violence in adolescent romantic relationships and improving related risk-reducing factors.
ENG